Optimization of Diffusion Bonding of Pure Copper (OFHC) with Stainless Steel 304L: . - Akbar, Ahmed Ali Akbar; Ajeel, Sami Abualnoun A; Hassoni, Safaa Mohammed (Al-Khwarizmi Engineering Journal, 2019)
This work deals with determination of optimum conditions of direct diffusion bonding welding of austenitic stainlesssteel type AISI 304L with Oxygen Free High Conductivity (OFHC) pure copper grade (C10200) in vacuum atmosphere of (1.5 *10-5 mbr.). Mini tab (response surface) was applied for optimizing the influence of diffusion bonding parameters (temperature, time and applied load) on the bonding joints characteristics and the empirical relationship was evaluated which represents the effect of each parameter of the process. The yield strength of diffusion bonded joint was equal to 153 MPa and the efficiency of joint was equal to 66.5% as compared with hard drawn copper. The diffusion zone reveals high microhardness than copper side due to solid solution phase formation of (CuNi). The failure of bonded joints always occurred on the copper side and fracture surface morphologies are characterized by ductile failure mode with dimple structure. Optimum bonding conditions were observed at temperature of 650 ◦C, duration time of 45 min. and the applied stress of 30 MPa. The maximum depth of diffuse copper in stainless steel side was equal 11.80 µm.